1999
DOI: 10.2306/scienceasia1513-1874.1999.25.195
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Mature zygotic embryos of Elaeis guineensis Jacq var tenera were excised and cultured on Eeuwens (1976Eeuwens ( , 1978 medium containing 2 mg/l 2,4-D. Callus was initiated from these embryos within 8 weeks. Embryoids were induced from the primary callus cultured on Murashige and Skoog (1962, MS) medium supplemented with 0.5 mg/l 2,4-D. For embryoid differentiation and plantlet regeneration, two successive media were employed. The first medium was MS-CAP devoid of 2,4-D but containing 0.05% activated charcoal .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…4d, e). The accumulation of starch grains in the somatic embryos provides an energy source for the development of embryos in oil palm (Kanchanapoom and Domyoas 1999). The histological sections in the present study also demonstrated formation of adventitious shoots from callus (Fig.…”
Section: Histological Analysissupporting
confidence: 76%
“…4d, e). The accumulation of starch grains in the somatic embryos provides an energy source for the development of embryos in oil palm (Kanchanapoom and Domyoas 1999). The histological sections in the present study also demonstrated formation of adventitious shoots from callus (Fig.…”
Section: Histological Analysissupporting
confidence: 76%
“…Three explants were sampled for each period. The materials sampled for histological studies were fixed in FAA 50 (formol: acetic acid: ethylic alcohol 50%, on 5:5:90 ratio) and conserved in 70% ethylic alcohol (Johansen 1940). The samples were embedded in methacrylate (Historesin-Leica) according to the manufacturer recommendations and sectioned transversally and longitudinally in 6 lm slices with a rotatory microtome.…”
Section: Histological and Histochemical Analysesmentioning
confidence: 99%
“…The samples were embedded in methacrylate (Historesin-Leica) according to the manufacturer recommendations and sectioned transversally and longitudinally in 6 lm slices with a rotatory microtome. The sections were then stained with toluidine blue O (O'Brien et al 1964) for metacromasy and stained with Lugol reagent (Johansen 1940) for starch detection. The slides were mounted in synthetic resin (Permount Ò ).…”
Section: Histological and Histochemical Analysesmentioning
confidence: 99%
“…On top of AC and putrescine, some other additives are frequently added to the culture medium. These include hydrolyzed casein (Kanchanapoom and Domyoas, 1999; Jayanthi et al, 2011, 2015; Thuzar et al, 2011; Corrêa et al, 2016; Gomes et al, 2016, 2017), the amino acids glutamine (Scherwinski-Pereira et al, 2010; Guedes et al, 2011; de Carvalho Silva et al, 2014; Gomes et al, 2016, 2017; Wan Nur Syuhada et al, 2016; Monteiro et al, 2017), asparagine and arginine (Jayanthi et al, 2015; Corrêa et al, 2016), ascorbic acid (Teixeira et al, 1995; Monteiro et al, 2017), and polyvinylpyrrolidone (Teixeira et al, 1994, 1995), added at variable concentrations.…”
Section: Oil Palm Somatic Embryogenesismentioning
confidence: 99%
“…While, with the exception of a few protocols (Kanchanapoom and Domyoas, 1999; Thuzar et al, 2011; Wan Nur Syuhada et al, 2016), cultures are kept in dark conditions during the EC induction phase, in around 50% of the protocols cultures are transferred to light conditions for induction and maturation of SEs. Regeneration is always performed in light conditions, with a photoperiod of 16 h d −1 and a photosynthetic photon flux varying between 20 and 60 μmol m −2 s −1 .…”
Section: Oil Palm Somatic Embryogenesismentioning
confidence: 99%